The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A340941 G.f. A(x) satisfies: A(x) = (A(x) - x)*(1 - x*A(x)) * Sum_{n>=0} x^n/(1 - x*A(x)^n). 7
 1, 1, 1, 3, 10, 36, 137, 545, 2244, 9500, 41151, 181736, 816085, 3718508, 17165117, 80172679, 378513020, 1804991424, 8688578508, 42199027520, 206723209249, 1021191612686, 5086213545738, 25540278088827, 129302804317291, 660055084179260, 3397896035465901 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,4 COMMENTS Equals row k = 0 of rectangular table A340940. LINKS FORMULA G.f. A(x) satisfies: (1) Sum_{n>=0} x^n/(1 - x*A(x)^n)  =  A(x)/((A(x) - x)*(1 - x*A(x))). (2) Sum_{n>=0} x^(2*n) * A(x)^(n^2) * (1 + x*A(x)^n) / (1 - x*A(x)^n))  =  A(x)/((A(x) - x)*(1 - x*A(x))). EXAMPLE G.f. A(x) = 1 + x + x^2 + 3*x^3 + 10*x^4 + 36*x^5 + 137*x^6 + 545*x^7 + 2244*x^8 + 9500*x^9 + 41151*x^10 + 181736*x^11 + 816085*x^12 + ... such that A(x)/((A(x) - x)*(1 - x*A(x)))  =  1/(1-x) + x/(1 - x*A(x)) + x^2/(1 - x*A(x)^2) + x^3/(1 - x*A(x)^3) + x^4/(1 - x*A(x)^4) + x^5/(1 - x*A(x)^5) + ... also A(x)/((A(x) - x)*(1 - x*A(x)))  =  (1+x)/(1-x) + x^2*A(x)*(1 + x*A(x))/(1 - x*A(x)) + x^4*A(x)^4*(1 + x*A(x)^2)/(1 - x*A(x)^2) + x^6*A(x)^9*(1 + x*A(x)^3)/(1 - x*A(x)^3) + x^8*A(x)^16*(1 + x*A(x)^4)/(1 - x*A(x)^4) + ... where A(x)/((A(x) - x)*(1 - x*A(x)))  =  1 + 2*x + 3*x^2 + 5*x^3 + 10*x^4 + 25*x^5 + 75*x^6 + 255*x^7 + 940*x^8 + 3660*x^9 + 14827*x^10 + 61927*x^11 + ... GENERATING METHOD. Note that iteration of the following equation does not converge to the g.f. A(x): A(x) = (A(x) - x)*(1 - x*A(x)) * Sum_{n>=0} x^n/(1 - x*A(x)^n); however, the coefficients of A(x) may be determined by the method described below. Let P(x) be a partial sum of the power series A(x), then the next term in the series can be determined as follows. (1) Start with P(x) = 1 + x, then the coefficient a(2)=1 of x^2 in A(x) appears as the coefficient of x^4 in (P(x)-x)*(1-x*P(x))*Sum_{n=0..4} x^n/(1 - x*P(x)^n) = 1 + x + 0*x^2 + 0*x^3 + 1*x^4 + ... (2) Set P(x) = 1 + x + x^2, then the coefficient a(3)=3 of x^3 in A(x) appears as the coefficient of x^5 in (P(x)-x)*(1-x*P(x))*Sum_{n=0..5} x^n/(1 - x*P(x)^n) = 1 + x + x^2 + 0*x^3 + 0*x^4 + 3*x^5 + ... (3) Set P(x) = 1 + x + x^2 + 3*x^3, then the coefficient a(4)=10 of x^4 in A(x) appears as the coefficient of x^6 in (P(x)-x)*(1-x*P(x))*Sum_{n=0..6} x^n/(1 - x*P(x)^n) = 1 + x + x^2 + 3*x^3 + 0*x^4 + 0*x^5 + 10*x^6 + ... (4) Set P(x) = 1 + x + x^2 + 3*x^3 + 10*x^4, then the coefficient a(5)=36 of x^5 in A(x) appears as the coefficient of x^7 in (P(x)-x)*(1-x*P(x))*Sum_{n=0..7} x^n/(1 - x*P(x)^n) = 1 + x + x^2 + 3*x^3 + 10*x^4 + 0*x^5 + 0*x^6 + 36*x^7 + ... Continue in this way to uniquely determine all the coefficients in g.f. A(x). PROG (PARI) {a(n) = my(A=1+x +x^3*O(x^n), H=A); for(k=1, n, A = (A-x)*(1-x*A) * sum(m=0, n+3, x^m / (1 - x*A^m +x^3*O(x^n)) ); A = truncate( H + polcoeff(A, k+2)*x^k ) +x^3*O(x^n); H=A); polcoeff(A, n)} for(n=0, 30, print1(a(n), ", ")) CROSSREFS Cf. A340940, A340942, A340894, A340895.. Sequence in context: A317775 A171753 A002212 * A149041 A307346 A202834 Adjacent sequences:  A340938 A340939 A340940 * A340942 A340943 A340944 KEYWORD nonn AUTHOR Paul D. Hanna, Feb 03 2021 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified August 3 13:59 EDT 2021. Contains 346438 sequences. (Running on oeis4.)